2017
DOI: 10.1038/s41598-017-04247-x
|View full text |Cite
|
Sign up to set email alerts
|

Helium Irradiation and Implantation Effects on the Structure of Amorphous Silicon Oxycarbide

Abstract: Despite recent interest in amorphous ceramics for a variety of nuclear applications, many details of their structure before and after irradiation/implantation remain unknown. Here we investigated the short-range order of amorphous silicon oxycarbide (SiOC) alloys by using the atomic pair-distribution function (PDF) obtained from electron diffraction. The PDF results show that the structure of SiOC alloys are nearly unchanged after both irradiation up to 30 dpa and He implantation up to 113 at%. TEM characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 40 publications
3
24
0
Order By: Relevance
“…Ion irradiation in SiOC may destroy high energy Si-O bonds and lead to formation of more Si-C bonds with low bonding energy. Indeed, it has been reported that ion irradiation results in a decreased number of Si-O bonds and an increased number of Si-C and C-O bonds in SiOC films [7]. In addition, more Si-C bonds are expected to form in SiOC with randomly dispersed C as compared to SiOC with aggregated C. It is conceivable that the irradiation-induced strengthening observed in present SiOC films can be attributed to an increase in Si-C bonds.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Ion irradiation in SiOC may destroy high energy Si-O bonds and lead to formation of more Si-C bonds with low bonding energy. Indeed, it has been reported that ion irradiation results in a decreased number of Si-O bonds and an increased number of Si-C and C-O bonds in SiOC films [7]. In addition, more Si-C bonds are expected to form in SiOC with randomly dispersed C as compared to SiOC with aggregated C. It is conceivable that the irradiation-induced strengthening observed in present SiOC films can be attributed to an increase in Si-C bonds.…”
Section: Discussionmentioning
confidence: 80%
“…Amorphous silicon oxycarbide (SiOC) ceramics are a group of superior radiation-tolerant materials suitable for applications in reactor-like harsh environments due to their exceptional thermal stability and irradiation resistance [1][2][3][4][5]. SiOC ceramics can retain their amorphous structure without crystallization, void formation or segregation under ion irradiation doses up to 20 displacements per atom (dpa) at temperatures up to 600 °C [1,2,[6][7][8]. Unlike crystalline solids, amorphous materials do not contain conventional crystal defects such as vacancies, interstitials or dislocations [9].…”
Section: Introductionmentioning
confidence: 99%
“…The thicknesses of analyzed pure Fe film, thin and thick SiOC/Fe multilayers were 68.2 ± 6.1, 74.1 ± 8.5 and 52.8 ± 4.2 nm. The detailed microstructure analysis of as-deposited SiOC film, Fe film and SiOC/Fe multilayers films can be found in previous references [28,29].…”
Section: Methodsmentioning
confidence: 99%
“…This model class of amorphous ceramics has exhibited great stability under irradiation, sustaining its glassy state over a wide range of irradiation conditions [14,15]. In addition, it has demonstrated the immunity of He bubble formation by continually removing He as it was implanted [16,17]. For instance, implanted He atoms were found to outgas from the SiOC matrix through atomic-scale diffusion without damaging its free surfaces, even at liquid nitrogen temperatures, resulting in time-invariant structure and properties.…”
Section: Introductionmentioning
confidence: 99%